Age distribution pattern of female breast cancer patients in Bangladesh- developing early and presenting late - Nessa, Ashrafun; Hussain, Tanvir; Alam, Syed M.; Faruk, Imtiaz; Jahan, Ishrat (International Surgery Journal, 2018)
Background: Carcinoma of the breast is the most common malignancy in females. At present carcinoma breast is the leading cancer in Bangladesh and is competing cancer cervix in incidence. Epidemiological studies at regional and global levels suggest the occurrence of carcinoma breast at a younger, premenopausal age in Indian and Asian women as compared with western women. Knowledge of this factor emphasizes the need to modify the timing of modalities of detection of early carcinoma and its management. According to literature, majority of carcinoma breast cases in the western countries present in Stages I and II of the disease whereas in Bangladesh majority cases present in Stage III of the disease. The objective of this study is to observe age of occurrence of breast cancer and stage of cancer in SSMC and MH. Methods: A cross sectional observational study was conducted in 34 patients of histopathologically confirmed breast cancer. Results: Mean age of subjects was 46.24±7.4 years. Age distribution showed peaks at 41-50 years with 18 patients. This study shows that 82.35% of the total patients were having advanced carcinoma breast (Stage III, IV) and 77% of these patients were below 50 years of age. Conclusions: Breast cancer is increasingly occurring in younger age groups in Bangladesh when compared with western countries and a more aggressive nature of the disease strikes in their reproductive period suggesting the need for change in modalities of early cancer detection and adjusting preventive and therapeutic efforts. This small study may provocate thought for larger scale population study to evaluate the scenario in Bangladesh.